Oral pathology in children and adolescents with HIV on antiretroviral therapy highly active - Marquez Peña, George Paul (2016)
Objective: Determine oral pathologies in children and teenagers with human immunodeficiency virus (HIV) infection in antiretroviral therapy (HAART) according to their clinical and immunological status and characteristics of the receiving HAART. Materials and method: A descriptive, transversal and obser-vational study. 20 pediatric patients Hipolito Unanue National Hospital of both sexes between 2 and 13 years were evaluated. Pathologies were diagnosed by recommended by the Clearinghouse on Oral Problems related to HIV infection in the European Community and The Collaborating Center on Oral Manifestation of the Human Immunodeficiency Virus from The World Health Organization and classification of orofacial manifestations in system children with HIV Ramos et al. (1999) a database will be developed, using descriptive statistics. Results: The pathology was found herpes simplex (5 %), dental caries (100 %) and gingivitis (95 %). The 20 % of the whole population had Primary Dentition, with a “dmf index” of 7 ± 2. The other 80 % of the whole population had mixed dentition with “DMF” and “dmf” index of 5 ± 6,12 and 6,81 ± 5,58 respectively. With regard to the OHI-S Greene and Ver-milion index 85 % had a deficient level and 15 % had a regular level, with an average value of 2,52 ± 0,46. Conclusions: The minimal presence of HIV-associated oral pathology is attributed to HAART. It emphasized that the time and type of treatment are essential for the reconstitution of the immune system. Carious lesions and gingivitis are possibly related to poor oral hygiene in the sample studied.